2021
DOI: 10.3390/molecules26123650
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS Screening of Phenolic Compounds in Wild and Cultivated Grapes Vitis amurensis Rupr.

Abstract: This work represents a comparative metabolomic study of extracts of wild grapes obtained from six different places in the Primorsky and Khabarovsk territories (Far East Russia) and extracts of grapes obtained from the collection of N.I. Vavilov All-Russian Institute of Plant Genetic Resources (St. Petersburg). The metabolome analysis was performed by liquid chromatography in combination with ion trap mass spectrometry. The results showed the presence of 118 compounds in ethanolic extracts of V. amurensis grape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 82 publications
2
12
0
Order By: Relevance
“…Among the derivatives of different anthocyanidins, Mv-derivatives were the most abundant components in the three grape groups, which was in agreement with our previous research on V. vinifera cultivars [35] and East Asian species [18].The average percentages of Mv-derivatives in the skins of V. amurensis grapes (58%) and hybrids (56%) were significantly less than that in the three V. vinifera grape skins (80%) (Figure 4b), and was approximate for the average percentages of Pn-derivatives among the V. vinifera grapes (10%), V. amurensis grapes (8%) and hybrids (10%), while the average percentages of Dpderivatives, Cy-derivatives and Pt-derivatives in V. amurensis grapes (15%, 9% and 9%) and hybrids (19%, 6% and 9%) were obviously higher than those in the three V. vinifera grapes (4%, 1% and 5%). In addition, it has been confirmed that Pg-derivatives are present at trace concentrations in some grape cultivars of V. vinifera [36,37], V. amurensis [10,21], V. labrusca, V. aestivalis [18] and V. rotundifolia [38]. In this study, pg-derivatives were found in all the grapes assayed, accounting for 0.00046-0.10% of TA (Figure 4b).…”
Section: Composition Of Anthocyaninssupporting
confidence: 73%
See 3 more Smart Citations
“…Among the derivatives of different anthocyanidins, Mv-derivatives were the most abundant components in the three grape groups, which was in agreement with our previous research on V. vinifera cultivars [35] and East Asian species [18].The average percentages of Mv-derivatives in the skins of V. amurensis grapes (58%) and hybrids (56%) were significantly less than that in the three V. vinifera grape skins (80%) (Figure 4b), and was approximate for the average percentages of Pn-derivatives among the V. vinifera grapes (10%), V. amurensis grapes (8%) and hybrids (10%), while the average percentages of Dpderivatives, Cy-derivatives and Pt-derivatives in V. amurensis grapes (15%, 9% and 9%) and hybrids (19%, 6% and 9%) were obviously higher than those in the three V. vinifera grapes (4%, 1% and 5%). In addition, it has been confirmed that Pg-derivatives are present at trace concentrations in some grape cultivars of V. vinifera [36,37], V. amurensis [10,21], V. labrusca, V. aestivalis [18] and V. rotundifolia [38]. In this study, pg-derivatives were found in all the grapes assayed, accounting for 0.00046-0.10% of TA (Figure 4b).…”
Section: Composition Of Anthocyaninssupporting
confidence: 73%
“…Razgonova et al [10] identified 7 acylated derivatives, out of a total of 18 anthocyanin compounds, in V. amurensis grapes from Far East Russia. In this study, a richer group of acylated anthocyanin compounds (31) were detected (Table 2).…”
Section: Composition Of Anthocyaninsmentioning
confidence: 99%
See 2 more Smart Citations
“…MS/MS spectra of compounds produced fragment ion at m/z 304.054 [M-H-Hex], corresponding to taxifolin O -hexosides. Prominent fragment ions at m/z 259.061 [Agl-H-CO 2 ] − , 241.050 [Agl-H-CO 2 -H 2 O], and RDA ions at m/z 178.997 [ 1,2 A] − , 151.002 [ 1,3 A] − , 149.023 [ 1.3 B] − , and 125.023 [ 1,4 A] − confirmed the presence of taxifolin [ 36 ]. Based on the ratio between deprotonated molecular ion and fragments at m/z 304.054 [Y O - ] and 303.051 [Y O -H] − , the position of glycosylation of taxifolin can be distinguished ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%